Language change and linguistic theory. - Miller, D. Gary (Oxford University Press, 2011)
This book investigates a large range of changes and their motivations in all parts of the grammar and lexicon. The core argument is that, in the absence of a Grand Unification Theory in linguistics, a unified account of change is impossible without ignoring the bulk of natural language changes. Changes occur in successive formal grammars. Differences among successive I-languages constitute a change in the E‐language, but this work rejects the customary high premium on acquisition to the near exclusion of the role of adults and adolescents in the incrementation of change. Many innovations arise from competition in contact accommodation, but contact is only a catalyst. Features determine parametric variation and structures provide evidence (cues) for features. Since changes are typically not macroscalar, this work adopts a (micro)cue theory of parametric variation. The traditional view required a categorical (off/on) value setting. Through multiple binary cuts and different microcues, the new view permits a language to have, for instance, V2 in some structures but not others. With the reduction of UG (Universal Grammar) to a universal inventory of formal features, the once extravagant role of UG has been largely replaced by principles of efficient computation to explain crosslinguistically frequent changes. Additionally, neurolinguists have concluded that some constraints have evolved over time into a multilevel representation in the nervous system. Taking this and structure-building features into account, this work argues that some changes are grounded in synchronic cognitive constraints, a large number in principles of computation, many in extralinguistic factors, some in processing and functional motivations, and some just accidents of history.